The Hengill Triple Junction, Iceland: Classification of Tectonic Surface Features - Steigerwald, Louis, 1992- (2017)
The Hengill Triple Junction in Iceland is formed by the intersection of the Western Volcanic Zone (WVZ), Reykjanes Peninsula Oblique Rift (RPOR) and a transform zone, the South Iceland Seismic Zone (SISZ). The 19 x 13 km2 study area thus contains extensional structures related to volcanic systems of the two rift zones, Hengill and Hrómundartindur, as well as strike-slip structures characteristic of the transform zones. High definition aerial photographs, satellite images, and digital elevation models are used, supported by field studies, to accurately map and classify tectonic features in an effort to separate N-S trending strike-slip faults from the fissure swarms of the volcanic systems. A portion of the southern Hengill fissure swarm lies within the area. It trends NE-SW and exhibits extensional features characteristic of spreading ridges, i.e. normal faults, open fractures, and eruptive fissures. It is clearly delineated by surface fractures, and is traced a length of 28 km southwest from the central volcano, terminating before reaching the coastline. The fissure swarm is 2 - 3.5 km wide in the study area, widening southwards. Elevation profiles across the fissure swarm suggest a spreading rate comparable to the southern WVZ, which spreads at 4-5 mm/yr. East-west shearing in the RPOR and SISZ is accomplished by many smaller and less conspicuous, northerly oriented strike-slip faults in a ‘bookshelf faulting’ manner. These parallel faults are overprinted on the volcano-tectonic structures of the RPOR. Evidence of 11 northerly striking strike-slips faults is found within the study area. Þrjár greinar flekaskilanna á Suðvesturlandi mætast í þrískilum sem gjarnan eru kennd við Hengil. Greinarnar þrjár, sem allar hafa sín séreinkenni, eru skárekbelti Reykjanesskaga, vestara gosbeltið og skjálftabelti Suðurlands. Á rannsóknarsvæðinu að stærð 19 x 13 km2 sem var afmarkað umhverfis þrískilin, má finna sprungur og misgengi sem hafa einkenni allra svæðanna, bæði siggengi og gjár dæmigerð fyrir sprungusveima ...